Medidas de comprimento : uma sequência didática na perspectiva interdisciplinar para o ensino fundamental - Rech, Ivana Roberta (My University, 2025)
This dissertation is the report of a research about the elaboration, application and validation of a didactic sequence with interdisciplinary practices focused on teaching and learning length measurements for the fifth grade of elementary school in a private school in the city of Caxias do Sul. The research sought to answer the following guiding question: How did a didactic sequence with interdisciplinary practices focused on the reality of fifth grade students of elementary school contribute to the meaningful learning of the concepts of magnitudes and length measurements? The research carried out is of an applied nature and has a qualitative approach. In order to find the solution to the guiding question, a didactic sequence was elaborated based on the Theory of Meaningful Learning and with an interdisciplinary approach as a way to articulate, relate and integrate the knowledge of Portuguese Language, Art, Geography, Physical Education, History and Mathematics in the teaching and learning process, considering the maintenance of a disciplinary structure at specific moments in the pedagogical work. The teaching sequence was developed in 11 50-minute meetings in November and December 2023. Based on the analysis of data obtained through practical measurement activities, group work and questionnaires, among others, evidence of significant learning regarding the content of length measurements can be found. Thus, as an educational product of this research, a teaching sequence with interdisciplinary practices was generated that aims to contribute to teaching practices for the teaching of quantities and length measurements, focusing on the active participation of elementary school students in the construction of knowledge. [resumo fornecido pelo autor]
A presente dissertação é o relato de uma pesquisa acerca da elaboração, aplicação e validação de uma sequência didática com práticas interdisciplinares voltado ao ensino e à aprendizagem das medidas de comprimento para o quinto ano do ensino fundamental em uma escola privada no município de Caxias do Sul. A pesquisa buscou responder a seguinte questão norteadora: Como uma sequência didática com práticas interdisciplinares voltadas à realidade dos alunos do quinto ano do Ensino Fundamental contribuiu para a aprendizagem significativa dos conceitos de grandezas e medidas de comprimento?" A pesquisa realizada é de natureza aplicada e de abordagem qualitativa. Para encontrar a solução da questão norteadora foi elaborada uma sequência didática fundamentada na Teoria de Aprendizagem Significativa e com abordagem interdisciplinar como uma forma de articular, relacionar e integrar os conhecimentos de Língua Portuguesa, Arte, Geografia, Educação Física, História e Matemática no processo de ensino e aprendizagem, considerando a manutenção de uma estrutura disciplinar em momentos específicos no trabalho pedagógico. A sequência didática foi desenvolvida em 11 encontros de 50 minutos nos meses de novembro e dezembro de 2023. A partir da análise dos dados obtidos por meio de atividades práticas de medições, trabalhos em grupo e questionário, entre outros, pode-se encontrar evidências da ocorrência de aprendizagem significativa referente ao conteúdo de medidas de comprimento. Assim, como produto educacional dessa pesquisa foi gerada uma sequência didática com práticas interdisciplinares que visa contribuir com a prática docente para o ensino de grandezas e medidas de comprimento focando na participação ativa dos estudantes do Ensino Fundamental para a construção do conhecimento. [resumo fornecido pelo autor]
Keywords: Matemática (Ensino fundamental) - Estudo e ensino; Aprendizagem significativa; Abordagem interdisciplinar do conhecimento na educação; Mathematics (Elementary school) - Study and teaching; Meaningful learning; Interdisciplinary approach in education